Control of nonlinear jacketed continuous stirred tank reactor using different control structures. (December 2021) - Siddiqui, Mohammad Atif; Anwar, Md. Nishat; Laskar, S.H.
Abstract: This study presents the control of the nonlinear model of a continuous stirred tank reactor (CSTR) through different control structures. The structures considered are single feedback configuration (SFC), cascade control configuration (CCC) and sliding mode control (SMC). To design the controllers, the dynamic behaviour of CSTR with a recirculating jacket heat transfer system is modelled into a third order unstable transfer function. Efforts have been made for the first time to control the CSTR also through parallel control configuration (PCC). Model matching technique in low frequency region has been used to design the controllers of SFC, CCC and PCC. The SMC controller parameters are obtained using root-locus technique and by minimizing the performance index. To analyse the performance of CSTR in these structures, simulations are conducted using the nonlinear model equations of the CSTR. The performance is also compared with recently reported work. It is observed that CSTR has been satisfactorily controlled using these structures and the best performance has been obtained using CCC. Highlights: The nonlinear jacket continuous stirred tank reactor (CSTR) is control through different structures. The structure used are single feedback configuration (SFC), cascade control configuration (CCC), sliding mode control (SMC) and parallel control configuration (PCC). The controllers of SFC, CCC and PCC are designed by model matching technique in the frequency region. The SMC controller parameters are obtained by using CSTR model parameters, root-locus technique and minimizing the performance index. Finally, simulation are conducted and compared with the other methods from the literature.